2015
DOI: 10.3325/cmj.2015.56.272
|View full text |Cite
|
Sign up to set email alerts
|

Performance of several simple, noninvasive models for assessing significant liver fibrosis in patients with chronic hepatitis B

Abstract: AimTo compare the performance of several simple, noninvasive models comprising various serum markers in diagnosing significant liver fibrosis in the same sample of patients with chronic hepatitis B (CHB) with the same judgment standard.MethodsA total of 308 patients with CHB who had undergone liver biopsy, laboratory tests, and liver stiffness measurement (LSM) at the Southwest Hospital, Chongqing, China between March 2010 and April 2014 were retrospectively studied. Receiver operating characteristic (ROC) cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
4
15
0
Order By: Relevance
“…Zeng et al showed that Fibro-Q had poor predictive value and was 0.569 of AUC (44). The current results showed that if Fibro-Q was above 2.26 for predicting significant fibrosis, AUC was 0.856.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 49%
See 1 more Smart Citation
“…Zeng et al showed that Fibro-Q had poor predictive value and was 0.569 of AUC (44). The current results showed that if Fibro-Q was above 2.26 for predicting significant fibrosis, AUC was 0.856.…”
Section: U N C O R R E C T E D P R O O Fsupporting
confidence: 49%
“…Some researchers found that AUC of API was 0.680 and 0.580 (43,44). The other ones also showed that AUC of API was 0.767 and 0.529 for 3.5 and 5.5 cut off values, respectively (34,37).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 98%
“…These methods are economically inexpensive and convenient, but their diagnostic accuracy and sensitivity are not high . Although these non‐invasive markers were first used to assess fibrosis in chronic hepatitis C (CHC) patients, they have also been applied to patients with CHB . Several diagnostic algorithms combining different fibrosis models have been proposed to detect liver fibrosis in CHC patients, and showed excellent diagnostic performance compared with individual models.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Although these non-invasive markers were first used to assess fibrosis in chronic hepatitis C (CHC) patients, 12,17,22 they have also been applied to patients with CHB. [24][25][26][27][28][29][30] Several diagnostic algorithms combining different fibrosis models have been proposed to detect liver fibrosis in CHC patients, and showed excellent diagnostic performance compared with individual models. However, similar algorithms that can be applied to CHB patients are very rare.…”
Section: Introductionmentioning
confidence: 99%
“…In liver damage, an increase in PT/INR ratio and a decrease in albumin level have been observed (31). In a study on the role of laboratory tests in the identification of fibrosis in CHB patients, platelet count, AST, ALT, GGT, ALP, total bilirubin, albumin, and INR were compared between patients with liver fibrosis stages 0 -1 and 2 -4; these parameters were found to be significantly different between the groups with respect to fibrosis stage (32). In another study, age, INR, AST, and GGT were associated with liver fibrosis stage (21).…”
Section: Discussionmentioning
confidence: 99%